New species of endecous (grylloidea, phalangopsidae, luzarinae) from the Iguaçu National Park (Brazil), including bioacoustics, cytogenetic and distribution data - Souza-Dias, Pedro G. B.; Szinwelski, Neucir; Fianco, Marcos; De Oliveira, Elliott Centeno; Francisco, De A. G. De Mello [UNESP]; Zefa, Edison (Magnolia Press, 2017)
In this study we describe two new species of cavicolous-straminicolous crickets for southern Brazil. Endecous chape n. sp. and E. naipi n. sp. are sympatric crickets that inhabit the Atlantic Semideciduous Forest of the Iguaçu National Park and adjacent areas. The descriptions were based on morphological characters, mainly from male genitalia and tegmina of adult males. Furthermore, we describe the chromosomes and the calling song of one of the new species, E. chape n. sp., presenting a discussion about the morphology of the phallic complex of Endecous and a distribution map for the species of the genus. The type-material is deposited in the Museu de Zoologia da Universidade de São Paulo (MZSP), and in the Coleção de Insetos do Departamento de Zoologia (Zoology Department Insect Collection), Universidade Estadual Paulista-UNESP-Botucatu campus.
Keywords: Calling Song; Chromosomes; Cricket; Insect; Orthoptera; Taxonomy